Identification and Differential Abundance of Mitochondrial Genome Encoding Small RNAs (mitosRNA) in Breast Muscles of Modern Broilers and Unselected Chicken Breed - Bottje, Walter G.; Khatri, Bhuwan; Shouse, Stephanie A.; Seo, Dongwon; Mallmann, Barbara; Orlowski, Sara K.; Pan, Jeonghoon; Kong, Seongbae; Owens, Casey M.; Anthony, Nicholas B.; Kim, Jae K.; Kong, Byungwhi C. (Frontiers in Physiology, 2017)
Background: Small noncoding RNAs are mostly encoded by the nuclear genome. Thousands of small noncoding RNAs encoded by mitochondrial genomes, termed as mitosRNAs were recently reported in human, mouse and trout fish. In this study, we first identified chicken mitosRNAs in breast muscle using small RNA sequencing method and the differential abundance was analyzed between modern pedigree male (PeM) broilers (rapid growth and large muscle mass) and the foundational Barred Plymouth Rock (BPR) chickens (slow growth and small muscle mass). Methods: Small RNA sequencing was performed with total RNAs extracted from breast muscles of PeM and BPR (n=6 per group) using the 1x50 bp single end read method of Illumina sequencing. Raw reads were processed by quality assessment, adapter trimming, and alignment to chicken mitochondrial genome (GenBank Accession: X52392.1) using the NGen program further statistical analyses were performed using the JMP Genomics 8. Differentially expressed mitosRNAs between PeM and BPR were confirmed by quantitative PCR. Results: Totals of 183,416 unique small RNA sequences were identified as potential chicken mitosRNAs. After stringent filtering processes, 117 mitosRNAs showing greater than 100 raw read counts were abundantly produced from all 37 mitochondrial genes (except D-loop region) and the length of mitosRNAs ranged from 22 to 46 nucleotides. Of those, abundance of 55 mitosRNAs were significantly altered in breast muscles of PeM compared to those of BPR: all mitosRNAs were higher in PeM breast except those produced from 16S-rRNA gene. Higher mitosRNAs in PeM breast may be due to the higher mitochondrial contents. Our data demonstrate that in addition to 37 known mitochondrial genes, the mitochondrial genome also encodes abundant mitosRNAs, that may play an important regulatory role in muscle growth via mitochondrial gene expression control.